Peran Agama Kristen Dalam Menghadapi Kehidupan Masyarakat yang Majemuk - Siahaan, Tryona Loise; Saragih, Gloria Luisa; Nainggoloan, Mangido (CV. Rayyan Dwi Bharata, 2024)
This study aims to analyze the Role of Christianity in Facing the Life of a Pluralistic Society. Christianity is very important in the life of a pluralistic society today in order to build the country of Indonesia to be even better. This research method focuses on The method in this article uses library research. Library research and research have four stages, namely preparing the necessary equipment, preparing a working bibliography, organizing time and reading, or recording research materials (according to Zed, 2004) The data collection method uses the method of searching and collecting sources from various sources such as books, journals, and research that has been done. Library materials obtained from various references are analyzed critically and need to be analyzed thoroughly to support suggestions and ideas. The results of the study show that: 1 The Role of Religion.